Practical smooth minimum time trajectory planning for path following robotic manipulators - Qiang Zhang; Shu-Rong Li; Xiao-Shan Gao (2013 American Control Conference, 2013)
Previous computation approaches of smooth minimum time trajectory for path following robotic manipulators either cannot fully utilize the maximum ability of machines, fail to minimum machine time, or cannot be computed efficiently because of the nonlinearity of problem formulations. In this paper, an efficient computation approach is proposed that has been designed as solving a convex optimization problem to generate smooth minimum time trajectory while utilizing the maximum ability of machines.